Rotation-traction manipulation induced intradiskal pressure changes in cervical spine—an in vitro study - Han, Changxiao; Feng, Minshan; Wen, Haibao; Yin, Xunlu; Li, Jing; Du, Wuyin; Peng, Bochen; Liu, Guangwei; Zhu, Liguo (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: Evaluate the effect of rotation-traction manipulation on intradiskal pressure in human cervical spine specimen with different force and duration parameters, and compare the intradiskal pressure changes between rotation-traction manipulation and traction.Methods: Seven human cervical spine specimens were included in this study. The intradiskal pressure was measured by miniature pressure sensor implanting in the nucleus pulposus. rotationtraction manipulation and cervical spine traction were simulated using the MTS biomechanical machine. Varied thrust forces (50N, 150N, and 250N) and durations (0.05s, 0.1s, and 0.15s) were applied during rotation-traction manipulation with Intradiscal pressure recorded in the neutral position, rotation-anteflexion position, preloading, and thrusting phases. Futuremore, we documented changes in intradiscal pressure during cervical spine traction with different loading forces (50N, 150N, and 250N). And a comparative analysis was performed to discern the impact on intradiscal pressure between manipulation and traction.Results: Manipulation application induced a significant reduction in intradiscal pressure during preloading and thrusting phases for each cervical intervertebral disc (P<0.05). When adjusting thrust parameters, a discernible decrease in intradiscal pressure was observed with increasing thrust force, and the variations between different thrust forces were statistically significant (P<0.05). Conversely, changes in duration did not yield a significant impact on intradiscal pressure (P>0.05). Additionally, after traction with varying loading forces (50N, 150N, 250N), a noteworthy decrease in intradiscal pressure was observed (P<0.05). And a comparative analysis revealed that rotation-traction manipulation more markedly reduced intradiscal pressure compared to traction alone (P<0.05).Conclusion：Both rotation-traction manipulation and cervical spine traction can reduce intradiscal pressure, exhibiting a positive correlation with force. Notably, manipulation elicits more pronounced and immediate decompression effect, contributing a potential biomechanical rationale for its therapeutic efficacy.